RELIGIOUS MODERATION IN THE FRAMEWORK OF CULTURAL RESERVATION IN BANJARPANEPEN BANYUMAS - Supriyanto supriyanto; Ahmad Muthohar Sa’idi; Hendri Purbo Waseso (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
This article aims to describe cultural reservation in Banjarpanepen Banyumas which is positioned as a mode for the application of religious moderation. Field data were collected through interviews, observations and documentation and then analyzed qualitatively. The findings are (a) cultural reservation in Banjarpanepen classified in two forms, namely traditional culture such as takiran 1 sura and bathing rituals at Kali Cawang on the full moon night and arts culture such as the lumping horse (ebeg) and Banyumasan lengger; (b) the values of religious moderation that arise in the cultural reservation process in Banjarpanepen are the high level of togetherness in the community and cooperation in religious activities; and (c) the Banjarpanepen community viewed from the cultural reservation process carried out shows an inclusive religious attitude by not excluding tradition as something that is unlawful and prohibited.